Binding Study of Vanadium and Uranium Complexes with Amidoxime Ligands at different pH. Issue 40 (26th October 2021) - Joshi, Ruma
Abstract: Different NMR spectroscopic techniques were used to characterize the uranyl (UO2 +2 ) and vanadium(V) complexes of glutarimidedioxime and glutardiamidoxime formed in solution. Stability of vanadium(V)‐glutarimidedioxime in the presence of UO2 +2 at different PH were investigated. Abstract : Synopsis The solution phase complexes of uranium and vanadium(V), with amidoxime ligands, glutarimidedioxime and open‐chain glutardiamidoxime were characterized. Competition of vanadium(V) with uranyl ions in aqueous solution was studied. Spectroscopic techniques, 1 H, 13 C and 51 V NMR (Nuclear Magnetic Resonance) spectroscopy were used for characterization of solution phase uranyl and vanadium complexes, and to evaluate the relative stabilities of such complexes at different pH values.